Stability of large-scale discrete systems under structural perturbations - Martynyuk, A. A.; Miladzhanov, V. G.; Muminov, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
By using the matrix Lyapunov function, we establish conditions of (uniform) stability and (uniform) asymptotic stability of a large-scale discrete system under structural perturbations.